KOLABORASI MAHASISWA DAN PT PROXI DALAM PENGEMBANGAN KEAHLIAN KEAMANAN JARINGAN UNTUK MENDUKUNG TRANSFORMASI DIGITAL YANG AMAN - Tirawati, Tirawati; Insany, Gina Purnama (Lembaga Pendidikan dan Penelitian Manggala Institute, 2025)
This community service activity aims to improve students competence in network security strategies through collaboration with PT Proxi, an internet service provider company. This training focuses on the use of MikroTik devices and Winbox applications for firewall configuration as an effort to improve network security. Simulations are carried out using a simple topology between MikroTik and laptop devices to implement network filtering with certain rules. The results of this activity show that the firewall configuration is able to block access to unwanted sites or IP addresses, increasing protection against cyber threats. Thus, this activity is expected to not only increase student capacity but also provide benefits to the community in supporting a safer and more sustainable digital transformation.